1996
DOI: 10.1007/s004030050103
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of superficial basal cell carcinomas using topically applied delta-aminolaevulinic acid and a filtered xenon lamp

Abstract: Photodynamic therapy is well suited to the treatment of SBCCs giving good cosmetic results regardless of lesion size. The filtered xenon lamp proved to be particularly suitable for photodynamic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 0 publications
0
41
0
3
Order By: Relevance
“…The clinical studies listed in table 3 can be subdivided into those where irradiation was carried out with a laser [5, 9, 11, 14]and those where a filtered or unfiltered lamp was used [3, 10, 12, 13, 15]. The most important differences between a laser and a lamp are the narrow spectral distribution and the high degree of spatial collimation of the former.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical studies listed in table 3 can be subdivided into those where irradiation was carried out with a laser [5, 9, 11, 14]and those where a filtered or unfiltered lamp was used [3, 10, 12, 13, 15]. The most important differences between a laser and a lamp are the narrow spectral distribution and the high degree of spatial collimation of the former.…”
Section: Discussionmentioning
confidence: 99%
“…Another suggestion for achieving better penetration is the use of curettage before PDT. 22 Ongoing studies, for instance, show that intralesional application of ALA in aqueous solution 4 hours before exposure to light can lead to complete eradication of nonmelanoma skin cancer and a long-term disease-free state. 32 Furthermore, future studies will have to determine by direct comparison whether the use of monochromatic laser light is superior to that of polychromatic light in ALA-PDT.…”
Section: Commentmentioning
confidence: 97%
“…Wolf et al 5 previously reported a complete clinical response in 36 (97.3%) of 37 superficial BCC and 5 (83.3%) of 6 superficial SCC at 4 to 8 weeks after ALA-PDT. After a follow-up of 6 months, Wennberg et al 22 reported a 92% cure rate for superficial BCC and a 61% cure rate for Bowen disease by using a 20% ALA solution and a filtered xenon lamp as the light source. Lui et al, 23 who performed topical ALA-PDT with polychromatic visible light greater than 570 nm, achieved a clinical complete response in 7 (88%) of 8 superficial BCC and in 2 (67%) of 3 superficial SCC; in contrast, however, only 4 (50%) of 8 superficial BCC and 2 (67%) of 3 SCC achieved a complete histological response.…”
Section: Commentmentioning
confidence: 99%
“…42 A TFD também é considerada uma modalidade não invasiva para os CBCs superficiais, com vários estudos que suportam o seu uso. 28,[43][44][45] Em recente estudo multicêntrico conduzido por Basset-Seguin e cols, o índice de cura foi de 97% após 3 meses de seguimento. Em seguimento maior de 5 anos, a taxa de recorrência observada foi de 22%.…”
Section: Aplicações Clínicas Oncológicas Em Dermatologiaunclassified